Global sourcing and firm selection - Wilhelm Kohler; Marcel Smolka (University of Tübingen, Faculty of Economics and Social Sciences, 2013)
Which firms find it optimal to integrate their input suppliers into the firm boundaries of control (vertical integration)? Which firms choose to expand their sourcing activities across the national border (offshoring)? This letter provides novel evidence on these questions based on a Spanish firm-level data set. We find that firms selecting into strategies of vertical integration and of offshoring tend to have been more productive ex ante than firms choosing not to do so. This finding is in line with the recent heterogeneous-firm literature on input sourcing under incomplete contracts.
urn:nbn:de:bsz:21-opus-71054
Keywords: F14; F23; L22; L23; 330; vertical integration; offshoring; firm selection; firm productivity